Alocação de recursos orçamentários: um estudo sobre os municípios paranaenses - Santos, Antonio Marcos Flauzino dos (2017)
This thesis aims to analyze the public managers from Paraná’s decisions, based on the criteria utilized in decision making on the process of public budget elaboration, considering the budget rigidity. It is based on the notions of public budget, on its transformation and on the discussion about the budget rigidity. The models of decision making are presented, highlighting the incremental model which presents the characteristics utilized in public institutions. The research occurred in 5 cities in the northwest mesoregion of the Paraná state. For the data acquirement, semi-structured interviews were elaborated and utilized with the mayors and the accountants or the ones responsible for planning the city budget. For choosing and analyzing, the cities were divided into three categories, as: small, medium and large-sized, according to the region’s characteristics. It was verified that the managers elaborate the public budget prioritizing the mandatory spending for payroll and the ones associated with health and education. Regarding the budget rigidity, respondents agree with its existence so that the investments in those areas of priority are preserved. It is concluded that the decision making process, both in the moment of the budget proposal elaboration and in the budget execution, occurs in an incremental way, where decisions are made taking into consideration past experiences and also through the consensus between the actors involved in this process.